Tubularenes. Issue 31 (23rd July 2020) - Mirzaei, Saber; Castro, Edison; Sánchez, Raúl Hernández
Abstract : First scaffolding approach to obtain tubular-shaped contorted aromatic architectures. Abstract : We report the synthesis and characterization of conjugated, conformationally rigid, and electroactive carbon-based nanotubes that we term tubularenes. These structures are constructed from a resorcin[ n b ]arene base. Cyclization of the conjugated aromatic nanotube is achieved in one-pot eight-fold C–C bond formation via Suzuki–Miyaura cross-coupling. DFT calculations indicate a buildup of strain energy in excess of 90 kcal mol −1 . The resulting architectures contain large internal void spaces >260 Å 3, are fluorescent, and able to accept up to 4 electrons. This represents the first scaffolding approach that provides conjugated nanotube architectures.